(untitled) (Pubmet, 2022)
National Initiatives for Open Science in Europe (NI4OS-Europe) is a Horizon 2020 project, one of whose objectives is to promote the European Open Science Cloud (EOSC) and open science in 15 Central and East European EU states and EU associated countries. This paper describes the variety of NI4OS-Europe promoting activities carried out in Hungary by the Governmental Agency for IT Development (KIFÜ). All these activities aim at different, and sometimes overlapping groups and involve: ▸ publishing researcher interviews on research data management and open science practices for early career researchers; ▸ open science news feed for open science practitioners; ▸ publishing an e-learning course on EOSC and open science for graduate and PhD students; ▸ testing research data management (RDM) tools for the Hungarian research community; ▸ organising various events, including the Hungarian Open Science Forum targeting senior researchers and stakeholders; ▸ an EOSC Champion programme at three major Hungarian universities. Identifying good practices will give us the chance to find the best communication channels andmethods to promote open science and to manage expectations of funders, researchers, and librarians. We will analyse audience diversity at six NI4OS events organised as part of the project. The anonymized dataset based on registration forms will be filtered by affiliation and profession. We will attempt to identify the main event features that mostly attract librarians or researchers. We will test the hypothesis that open science is generally more welcomed by research institutions’ librarians than, researchers, whose interests are more attached to funds and applications. We will also study usage data of open science news feeds. Having around 200 posts and 5000 visitors from May 2021 to April 2022 gives us the chance to learn more about the characteristics of the most visited, event-related posts, followed by posts related to national policies, which are visited more frequently than international ones. The paper will also argue that bottom-up and top-down approaches of promoting EOSC need to be used in a delicate balance to reach out to the widest audience possible.